Identification of ESUs in the critically endangered portuguese minnow Chondrostoma lusitanicum Collares-Pereira 1980, based on a phylogeographical analysis - Robalo, Joana Isabel (2012)
In this paper, we analysed the phylogeography of the Critically Endangered fish Chondrostoma lusitanicum (Cyprinidae) endemic to Portugal. A fragment of the mitochondrial cyt b gene and one from the nuclear beta-actin gene were sequenced. The results support recognition of 3 ESU’s distributed as follows: 1) Sado River, 2) the Tagus River basin and 3 independent nearby coastal rivers (collectively named ‘‘West’’) and 3) Lagoa de Albufeira, a small coastal lagoon between Tagus and Sado basins.